Efficient nanoparticle transport via CO2 foam to stabilize oil in water emulsions. (15th September 2020) - Etemad, Sahand; Kantzas, Apostolos; Bryant, Steven
Highlights: Visualizing the Nanoparticle placement on oil/water interface. Demonstrating the improvement in the stability of CO2 foam using NP and surfactant mixtures. Generating O/W emulsion stabilized by Cellulose Nanocrystals initially presented in the foam. Reduction of particle surface charge after exposure to the oil and bringing them to the interface. Improving sweep efficiency and heavy oil recovery via NP fortified foam flooding. Abstract: When dealing with water flooding in viscous oil reservoirs, many adverse factors influence the expected degree of success. High relative mobility ratio results in early breakthrough and low cumulative oil recovery. Moreover, alkanoic acids present in the oil are very effective adsorbing agents to water/oil interfaces, which stabilize water in oil (W/O) emulsions. These emulsion droplets can dramatically increase the viscosity of the oil and increase pumping costs. The above-mentioned concerns are the motivation to try generating preferentially oil in water (O/W) emulsions in situ, thereby improving mobility ratio. We introduce biodegradable Cellules Nanocrystal (CNC) particles previously shown to stabilize O/W emulsions. Delivering the nanoparticles into the reservoir with greater sweep efficiency is a key challenge. Here we have explored the use of nanoparticle-stabilized foam for this purpose. The results have shown that the NP system improves the recovery in two aspects: First, it stabilizes foam that delivers CO2 gas with greater sweep efficiency. High quality foam encompasses a large bubble density and imposes enhanced resistance against the gas flow, which increases the sweep efficiency. Secondly, as the foam displaces oil, nanoparticles that were originally present within the foam structure transferred into oil/water interfaces, enabling the in-situ creation of O/W emulsions stabilized by the nanoparticles.